Martingale convergence theorems in JW-Algebras - Karimov , Abdusalom; Mukhamedov, Farrukh (School of Mathematical Sciences, Universiti Sains Malaysia, 2010)
In this paper certain properties of conditional expectations of re-versible JW-algebra A with a faithful semifinite normal trace are studied. As an application of these results, we prove convergence theorems for supermartin- gales and martingales defined on such algebras.